2002
DOI: 10.1179/016164102101199738
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of inhibiting both blood and vascular selectins after stroke and reperfusion

Abstract: Early intervention after acute ischemic stroke is essential to minimize brain cell injury. Although reperfusion of the ischemic brain is the treatment of choice for acute stroke, reperfusion itself may cause additional injury. The inflammatory cascade, characterized in part by early leukocyte interaction with endothelium, may contribute to this additional injury to blood vessels and surrounding brain tissue, extending the area of infarction. The selectin family of adhesion molecules mediates the initial, rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Treating rabbits exposed to transient focal brain ischemia with an L-selectin antibody did not affect stroke outcome (Yenari et al, 2001). However, fucoidin, an inhibitor of both P-and L-selectin, significantly reduced infarct size and improved neurological function in experimental stroke in rats, but these observations could have been due to inhibition of P-selectin rather than Lselectin (Ruehl et al, 2002).…”
Section: Selectinsmentioning
confidence: 91%
“…Treating rabbits exposed to transient focal brain ischemia with an L-selectin antibody did not affect stroke outcome (Yenari et al, 2001). However, fucoidin, an inhibitor of both P-and L-selectin, significantly reduced infarct size and improved neurological function in experimental stroke in rats, but these observations could have been due to inhibition of P-selectin rather than Lselectin (Ruehl et al, 2002).…”
Section: Selectinsmentioning
confidence: 91%
“…Pre-clinical studies have demonstrated that inhibition of brain leukocyte infiltration using agents directly blocking adhesion molecules (e.g., CD11b/CD18, ICAM-1, P-selectin) and neutrophil inhibitory factor inhibition [Table 2] reduces infarct size, edema, and neurological deficits in transient MCAO models, even administrated up to 12–24h after ischemia, but the benefits do not extend to permanent stroke models [188,189,190] . Additionally, development of an anti-inflammatory milieu, and generation of pro-survival factors fostering tissue reconstruction and repair may be another useful therapeutic strategy.…”
Section: Anti-inflammatory Therapeutic Approaches For Ischemic Strokementioning
confidence: 99%
“…Recent reports suggest that prostaglandin E2EP1 receptors may be the downstream effectors responsible for neurotoxicity of COX-2 in ischemic stroke, and inhibitor of EP1 receptor has shown significant protection when administered 6 h after MCAO [335]. Fucoidin, an inhibitor of both P-and Lselectin, significantly reduced infarct size and improved neurological function in experimental stroke and reperfusion in rats [336]. Overexpression or treatment with IL-1 receptor antagonist (IL-1ra), an endogenous inhibitor of IL-1 reduces the infarct size [337,338], whereas mice deficient of IL-1ra exhibited a significant increase in ischemic damage [339].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%